2021
DOI: 10.2174/1567202619666211217140954
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Peroxisome Proliferator-activated Receptor Gamma (PPARγ) Agonist and PPAR Gamma Co-Activator 1α (PGC-1α) Activator Ameliorates Cognitive Deficits, Oxidative Stress, and Inflammation in Rodent Model of Parkinson’s Disease

Abstract: Background: PPAR gamma co-activator 1α (PGC-1α) is known as the master regulator of mitochondrial biogenesis. It is also a co-activator of peroxisome proliferator-activated receptor-gamma (PPARγ) and plays a role in preventing mitochondrial dysfunction in several neurodegenerative disorders, including Parkinson’s disease (PD). Depletion in the levels of these proteins has been linked to oxidative stress, inflammation, and DNA damage, all of which are known to contribute to the pathogenesis of PD. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…10 C). PGC-1α and PGC-1ß serve pivotal functions in metabolic control (Handschin & Spiegelman 2006) and, importantly, have been implicated in dopamine neuron survival (Jiang et al , 2016) and the pathogenesis of PD (Zheng et al , 2010; Su et al , 2015; Piccinin et al , 2021; Das et al, 2021; Jamwal et al , 2021). Similar roles have been ascribed to PPAR-α (Gottschalk et al , 2021; Avagliano et al , 2016), PEA’s primary receptor and obligatory PGC-1α partner (Handschin & Spiegelman 2006).…”
Section: Discussionmentioning
confidence: 99%
“…10 C). PGC-1α and PGC-1ß serve pivotal functions in metabolic control (Handschin & Spiegelman 2006) and, importantly, have been implicated in dopamine neuron survival (Jiang et al , 2016) and the pathogenesis of PD (Zheng et al , 2010; Su et al , 2015; Piccinin et al , 2021; Das et al, 2021; Jamwal et al , 2021). Similar roles have been ascribed to PPAR-α (Gottschalk et al , 2021; Avagliano et al , 2016), PEA’s primary receptor and obligatory PGC-1α partner (Handschin & Spiegelman 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Promising results from preclinical studies reported that pioglitazone and rosiglitazone are able to ameliorate memory and cognitive impairment and decrease AD-related pathology in several rodent models of AD, including the 3xTg-AD mice and Tg2576 mice, by enhancing AKT signaling and attenuating tau hyperphosphorylation, neuroinflammation, and AD pathology [ 254 , 255 , 256 , 257 ]. Furthermore, pioglitazone, rosiglitazone and mitoglitazone were also shown to prevent dopaminergic neurodegeneration and locomotor deficits in MPTP-, STZ-, and 6-OHDA-lesioned rodent models of PD, by modulating the neuroinflammatory response in a neuroprotective fashion [ 258 , 259 , 260 , 261 , 262 , 263 , 264 ]. These findings are consistent with data from clinical studies.…”
Section: Regulation Of Metabolic Function As a Prevention Of Neurodeg...mentioning
confidence: 99%
“…Calculations were performed using the 2 −ΔΔCT method, and results were expressed as fold change relative to the sham group. 5 3.10. Isolation of the Mitochondria.…”
Section: Drug Administration and Treatmentmentioning
confidence: 99%
“…2−4 Various preclinical studies have previously targeted these pathophysiological alterations but with limited clinical success. 5,6 Therefore, there is always a need to look for newer approaches for PD treatment.…”
Section: Introductionmentioning
confidence: 99%